A comparative performance of columns: reinforced concrete, composite, and composite with partial C-FRP wrapping under contact blast. (2022) - Tahzeeb, Rafat; Alam, Mehtab; Muddassir, S.M.
Abstract: Damage to government buildings, iconic structures, and monuments from blast incidence of global terrorism and accidental explosions are perpetually attracting the attention of researchers. Devastating consequences associated with such a disastrous event of explosion inflict significant fatalities and huge economic losses. Efforts are being made by engineers and architects in the domain of blast-resistant design of structures to control the ensuing damage out of explosions. In the present study, an experimentally tested square reinforced concrete (RC) column with seismic lateral reinforcement carrying axial load subjected to an explosive charge of 100 kg ANFO (82 kg-TNT-equivalent) at a scaled distance of 1.0 m/kg 1/3 with 10 mm mesh size using the ABAQUS/CAE software equipped with concrete damage plasticity model is validated. Not many studies are available on the structural elements subjected to contact blasts. Columns being the most important load-carrying structural elements of the buildings, the effort is made to study the effect of contact blasts on the validated model. An RC composite column equivalent to the experimentally tested one is considered to enhance its blast response under contact blast. The composite column is further strengthened with C-FRP wrapping over the mid-height region subjected to the same blast loading. Performance of RC column, its equivalent composite column, and the equivalent composite column with partial C-FRP wrapping are analyzed and compared. In comparison of the RC column with top and bottom seismic reinforcements, maximum displacement and DDE of the equivalent composite column having top, bottom, and middle seismic reinforcements without C-FRP wrapping reduced by 61.21% and 48.12%, respectively. The percentage reductions of these values of the composite column with the wrapping are 89.93% and 87.03%, respectively. This research shows that the composite column with top, bottom, middle seismic reinforcement and with C-FRP wrapping gives the best performance under contact blast.